Newly acquired complete right bundle branch block early after heart transplantation is associated with lower survival - Rahm, Ann-Kathrin; Helmschrott, Matthias; Darche, Fabrice Fernand; Thomas, Dierk; Bruckner, Thomas; Ehlermann, Philipp; Kreußer, Michael; Warnecke, Gregor; Frey, Norbert; Rivinius, Rasmus (ESC heart failure, 2021)
Aims Right bundle branch block (RBBB) after heart transplantation (HTX) is a common finding, but its impact on post-transplant survival remains uncertain. This study investigated the post-transplant outcomes of patients with complete RBBB (cRBBB) ≤ 30 days after HTX. Methods This registry study analysed 639 patients receiving HTX at Heidelberg Heart Center between 1989 and 2019. Patients were stratified by diagnosis of cRBBB ≤ 30 days after HTX. Analysis included recipient and donor data, medication, echocardiographic features, graft rejections, atrial fibrillation, heart rates, permanent pacemaker implantation and mortality after HTX including causes of death. Results One hundred thirty-nine patients showed cRBBB ≤ 30 days after HTX (21.8%), 20 patients with pre-existing cRBBB in the donor heart (3.2%) and 119 patients with newly acquired cRBBB (18.6%). Patients with newly acquired cRBBB had a worse 1-year post-transplant survival (36.1%, P < 0.01) compared with patients with pre-existing cRBBB (85.0%) or without cRBBB (86.4%), along with a higher percentage of death due to graft failure (P < 0.01). Multivariate analysis indicated cRBBB ≤ 30 days after HTX as significant risk factor for 1-year mortality after HTX (HR: 2.20; 95% CI: 1.68-2.87; P < 0.01). Secondary outcomes showed a higher rate of an enlarged right atrium (P = 0.01), enlarged right ventricle (P < 0.01), reduced right ventricular function (P < 0.01), 30-day atrial fibrillation (P < 0.01) and 1-year permanent pacemaker implantation (P = 0.02) in patients with cRBBB after HTX. Conclusions Newly acquired cRBBB early after HTX is associated with increased post-transplant mortality.
First published: 02 July 2021
Gesehen am 31.08.2021